Dietary Pentosanase Supplementation of Diets Containing Different Qualities of Wheat on Growth Performance and Metabolizable Energy of Turkey Poults - Jr, A.A. Santos; Ferket, P.R.; Grimes, J.L.; Edens, F.W. (International Journal of Poultry Science, 2003)
Wheat varies in apparent metabolizable energy N-corrected (AMEn) due to the presence of non-starch polysaccharides (NSP), which can be improved by dietary enzyme supplementation. Poults from 0-17 d-age were fed diets containing various wheat sources (WS) with or without Natugrain Blend® (NB) (BASF, Germany). Five replicate cages of 10 poults were assigned to each eight-soybean-meal/wheat treatment diets and a control soybean-meal/corn diet. The treatments were a factorial arrangement of 4 WS (A, B, C, D) and 2 enzyme levels (0 and 200 mg NB/kg). The WS differed by the degree of frost damage during seed development. Regardless of the source of wheat, NB increased 17 d BW (351 vs 381 g, P < 0.001), decreased 1-17 d FCR (1.55 vs 1.49, P < 0.05), increased AMEn (2,204 vs 2,455 kcal/kg, P < 0.001), and increased apparent nitrogen retention (ANR) (35.0 vs 41.4 %, P < 0.05). No effects of WS were seen on growth performance, but WS A and B had higher (P < 0.05) AMEn than sources C and D (2,396 and 2,460 vs 2,246 and 2,216 kcal/kg, respectively). Gut viscosity was higher (P < 0.05) in poults fed wheat-based diets than the control diet. Enzyme supplementation to the wheat-based diets decreased viscosity (5.57 vs 3.98 cP, P < 0.05) to a level similar to the corn-based control diet, and it resulted in equivalent growth performance. Viscosities were negatively correlated with AMEn. The results demonstrated a positive effect of enzyme supplementation on nutrient utilization and performance of turkeys.